Three essays on corporate finance - Selvam, Srinivasan (2016)
In essay one, we examine how employee layoffs, actions that lower a firm’s social performance, affect stakeholder wealth and post-layoff contract terms with stakeholders. We find that although layoff-performance sensitivity is similar between firms with high and low corporate social responsibility (CSR) performance, high CSR firms’ shareholders, bondholders, and suppliers realize more negative layoff announcement returns than those of low CSR firms. High CSR firms also experience greater deterioration of supplier relationships and larger increases in loan rates and covenant numbers post layoffs. The results suggest that a firm’s commitment to fair stakeholder treatment affects its value and future stakeholder relationships. In essay two, we examine restructuring activities of family and non-family firms during the 2007 to 2009 economic crisis. Using hand-collected data on restructuring activities, we find that family firms are less likely to engage in ineffective downsizing and ineffective CEO turnover activities than non-family firms. These results are more pronounced for family firms managed by founding family CEOs. Family firms are also less likely to enter into unrelated businesses. Despite family firms’ reluctance to downsize, those that choose to do so during the crisis experience more positive stock market reactions to downsizing announcements and outperform in the post-crisis period. Our findings show that in response to the crisis, family firms undertake restructuring actions that improve firm value, suggesting that corporate ownership is an important factor that influences firms’ restructuring decisions. In essay three using major industry-level tariff reductions as the measure of customer industry competition, I examine the effect of such competition on customer-supplier trading relationships. I find that customers facing stiff competition strengthen their relationships with existing suppliers by increasing product purchases from the suppliers and maintaining post-tariff longer relationship duration, allowing the suppliers to improve their post-tariff performance. These results are concentrated in suppliers that have stronger pre-tariff relationship ties and those that are financially constrained. However, the increased purchases from financially constrained suppliers affect customer performance negatively in the post-tariff period. Overall, these results suggest that increased customer competition has both intended and unintended consequences for their trading relationships and their future performance.